An Investigation of Situational and Dispositional Antecedents of Faking Intentions in Selection Interviews - Bill, Benedikt; Melchers, Klaus G.; Buehl, Anne-Kathrin; Wank, Sabine (Frontiers in Psychology, 2020)
Applicants use faking in selection interviews to create a favorable impression and to increase their chances for a job offer. Theoretical models assume that such a behavior is influenced by situational and dispositional variables. However, previous research has mainly focused on dispositional variables whereas research about situational variables is sparse. To address this gap, we conducted three studies in which we examined how competition for a job and informing interviewees that information from their answers will be verified can influence faking intentions. Furthermore, we wanted to know whether these situational variables are able to explain additional variance in faking intentions beyond dispositional variables and whether there are interactions between situational and dispositional variables. In Study 1, we only found that high competition led to slightly higher faking intentions than low competition in a student sample. In Study 2, only a warning about the verification of applicants’ answers led to slightly lower faking intentions compared to no warning concerning verification in a working sample. Furthermore, faking intentions were lower in Study 2 than in the student sample in Study 1. In Study 3, we found no impact of our situational variables in a combined sample of students and non-students. We only found slightly higher honest impression management intentions in the high competition and the verification warning condition. We also found hardly any support for interaction effects between the situational and dispositional variables. Furthermore, the situational variables did not explain additional variance beyond the dispositional variables in any of the three studies. Possible reasons for the non-significant or small effect sizes for the situational variables can be found in a qualitative analysis of answers to an open-ended question in Study 3. However, we found that Honesty-humility und all facets of the Dark Triad were related to faking intentions. These results indicate that dispositional variables in particular have an impact on faking intentions.